TaqMan probe based multiplex quantitative PCR assay for determination of bovine, porcine and fish DNA in gelatin admixture, food products and dietary supplements - Sultana, Sharmin; Hossain, M.A. Motalib; Azlan, Azrina; Johan, Mohd Rafie; Chowdhury, Zaira Zaman; Ali, Md. Eaqub (Elsevier, 2020)
Detection of animal materials in gelatin-based products is required to address religious and cultural concerns, because porcine and bovine gelatins are prohibited in Halal, Kosher and Hindus consumer goods. In this paper, multiplex quantitative polymerase chain reaction (qPCR) assay using TaqMan probe was developed to discriminate bovine, porcine and fish gelatin species in a single assay platform. The assay was specific to cattle, pigs and fish, having been tested against 14 non-target species. The limit of detection, under gelatin admixed conditions, was 0.005 ng/µL. Finally, a pilot survey was undertaken testing 35 Halal branded processed food and dietary items. Out of 35 samples, only two were found to be positive for porcine species. The authenticity of these two qPCR products was confirmed by DNA sequencing analysis, which showed 99–100% similarity with Sus scrofa (Wild boar) species. © 2020 Elsevier Ltd